Training Model for Prospective Police Technical Staff to Be Assigned to the Republic of Indonesia's Overseas Diplomatic Missions - Arfiansyah, Taufik Hidayat; Giyanto, Bambang (International Journal of Science and Society, 2024)
This study evaluates and designs a training model for prospective Police Technical Staff to be assigned to the Republic of Indonesia's overseas diplomatic missions. The training model aims to enhance technical competence, cultural adaptation, and diplomatic skills, which are crucial for addressing complex challenges in the international environment. Through a literature review approach, this article highlights the importance of training needs analysis involving collaboration with various external stakeholders. The structured training program design includes task simulations, experiential learning, and continuous evaluation. The findings indicate that current training is suboptimal due to the dominance of one-way lecturing methods without distinguishing individual needs. Therefore, the ideal training strategy includes strengthening practical interactions, developing adaptive modules, and utilizing learning technologies. This holistic approach is expected to improve the performance of the Police Technical Staff, support the strategic role of the Indonesian National Police (Polri) at the international level, and enhance the quality of protection and services for Indonesian citizens abroad. With a more comprehensive training model, Polri can effectively respond to geopolitical dynamics and global challenges.